Response of Acer saccharum seedlings to elevated O3 and CO2 concentrations - Gaucher, Catherine; Dizengremel, Pierre; Mauffette, Yves; Chevrier, Normand (Phytoprotection, 2005)
The effects of three times ambient [O3] (3x) and high [CO2] (650 µL L-1 CO2) alone and in combination were studied on 2-yr-old sugar maple (Acer saccharum) seedlings for 86 days in open top chambers. Sugar maple net CO2 assimilation rate and growth were not decreased by the O3 treatment after one growing season, and the epicuticular wax was not damaged compared with the control. The absence of response to the O3 treatment is attributable to the low stomatal conductance of this species resulting in a low O3 uptake, together with the succession of periods of high and low [O3], which allowed the seedlings to alleviate the oxidative stress. At the end of August, under high [CO2], the growth of the seedlings and net CO2 assimilation to stomatal conductance to CO2 ratio in the second flush of leaves had doubled. Under the environmental growth conditions of the chambers (high light, nutrients and water availabilities), the seedlings may benefit from the availability of CO2. Sugar maple seedlings may have a competitive growth advantage under elevated CO2 conditions and three times ambient [O3] did not decreased the fertilizing effect of CO2.